Women rely on "gut feeling"? The neural pattern of gender difference in non-mathematic intuition. (October 2022) - Bao, Wei; Wang, Yunhong; Yu, Tingting; Zhou, Jiarong; Luo, Junlong
Abstract: Gender differences in intuition remain debatable. Previous research found an intuitive bias for women, but women's intuitive decision-makings sometimes were accurate. This study investigated behavioral and neural patterns of gender differences in intuition using the Embedded Chinese Character Task (ECCT) with event-related potentials. Participants judged whether a target character was included in a test character, which required either an intuitive process (the two characters were spatially separated/adjacent) or an analytical process (target characters were embedded in test characters). Women exhibited shorter reaction times and higher accuracy in intuitive materials for both inclusion and exclusion conditions. They elicited a larger P3b component with stronger parietal alpha power activity in the inclusion condition, and a larger P3b component in intuitive materials than men, indicating female preference for intuitive thinking in ECCT. Men elicited a larger N2 component with weaker parietal alpha power activity in the inclusion condition, indicating their preference for deliberative thinking in ECCT. The stereotype that women make wrong choices through intuitive thinking did not hold; instead, women demonstrated higher accuracy and faster speed than men in ECCT through intuition. The neural mechanism of gender difference in non-mathematic intuition is explained.